KEKUATAN SAMBUNGAN DUA TAMPANG PADA MDF DENGAN ALAT SAMBUNG PASAK WPC - Ali Murtopo; Elmi Nur Sayekti; Yudhi Arnandha (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2022)
MDF (Medium Density Fiberboard) and WPC (Wood Plastic Composite) are innovative results of using sawdust waste to overcome the problem of wood scarcity. This study used a WPC Teak dowel because it has high shear strength and does not cause rust marks. This study was conducted to determine the value of the MDF connection capacity using WPC Teak dowel connectors and to determine the connection failure mode based on the EYM (European Yield Model) theory. This study used a WPC Teak dowel with a diameter of 6 mm, 8 mm, 10 mm, and 12 mm. The type of connection is a double-shear wooden joint using MDF. The test was carried out at the Structural Laboratory, Civil Engineering Department, Tidar University using a Compression Testing Machine to get the value of the connection capacity and test failure mode based on the MDF bearing strength and WPC Teak post failure referring to ASTM D764-97a. The test results obtained an average connection capacity value WPC dowel with a diameter of 6 mm, 8 mm, 10 mm, and 12 mm, respectively, which was 1094 N; 1870 N; 2439 N; and 3462. The highest average connection capacity value at 12 mm diameter was 3462 N, and the lowest at 6 mm was 1094 N.